Relationship between Satisfaction and Academic Performance of Students at the College of Education - Ebenezer, Kwakwa; Adiyaa, Osei; Kumabia, Francis Koku Ras (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study was a correlational research design. It was designed for investigating the relationship between students’ satisfaction and academic performance among level 200 students of Mount. Mary College of Education in the Eastern Region of Ghana. Purposive sampling technique was used to sample 200 students. Satisfaction of Colleges of Education students were measured using adapted Student Satisfaction Survey developed by Strachota (2006) on a 4 point Likert scale (from Not Satisfied (1), Somehow Satisfied (2), Satisfied (3) and Highly Satisfied (4)) which has 8 items. Examination scores of four core subjects (Assessment in Basic Schools, Curriculum Studies, English Language Studies II, Forms and Functions of English Clause) in the first and second semesters of the 2020/2021 academic year were used to measure students’ academic performance.